Matrix-assisted diffusion-ordered spectroscopy application of surfactant solutions to the resolution of isomer spectra - Tormena, Cláudio F (Magnetic resonance in chemistry : MRC, 2012)
Copyright © 2012 John Wiley & Sons, Ltd.